2018
DOI: 10.3389/fpsyg.2018.00144
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Validation of the Bergen–Yale Sex Addiction Scale With a Large National Sample

Abstract: The view that problematic excessive sexual behavior ("sex addiction") is a form of behavioral addiction has gained more credence in recent years, but there is still considerable controversy regarding operationalization of the concept. Furthermore, most previous studies have relied on small clinical samples. The present study presents a new method for assessing sex addiction-the Bergen-Yale Sex Addiction Scale (BYSAS)-based on established addiction components (i.e., salience/craving, mood modification, toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
61
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 104 publications
15
61
2
5
Order By: Relevance
“…Specifically, we found single factor accounted for 62.31% of the total variance. Also, the instrument yielded high content validity that was consistent with previous studies, despite different sample sizes, race or cultures, and different translations (such as the study According to the psychometric properties of this study, it shows that BYSAS was highly test-retest reliable (2-week) for screening of sexual addiction and Cronbach's alpha was for internal consistency coefficient of 0.88 and for the intra-class correlation coefficient of 0.89 that was higher than the values obtained in previous reliable studies (9,16). In addition, the positive and significant correlations found in the Christon et al, study that indicated the high reliability of BYSAS.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Specifically, we found single factor accounted for 62.31% of the total variance. Also, the instrument yielded high content validity that was consistent with previous studies, despite different sample sizes, race or cultures, and different translations (such as the study According to the psychometric properties of this study, it shows that BYSAS was highly test-retest reliable (2-week) for screening of sexual addiction and Cronbach's alpha was for internal consistency coefficient of 0.88 and for the intra-class correlation coefficient of 0.89 that was higher than the values obtained in previous reliable studies (9,16). In addition, the positive and significant correlations found in the Christon et al, study that indicated the high reliability of BYSAS.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the results concerning the one-factor structure analysis model with six subscales are consistent with the previous studies funding from Norway (9) and Italy (17) that investigated the psychometric properties of the instrument. Also, our study indicated that the favorable relationship of all markers of the model with their substrates and strong association between its subscales, and appears suitable for the evaluating of the partial and general indices and specifically known for sexual addiction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The aim was to extend Andreassen et al's (2018) study to Israeli men by assessing the relationship between personality traits and the risk of sexual addiction, as well as extending their work by determining whether the risk for sexual addiction is associated with sexual orientation. Given that the present study was conducted with Israeli men, the instrument developed by Andreassen et al (2018), the BYSAS, had to be translated and validated in Hebrew, serving another objective of the study. Additionally, two hypotheses were tested in the present study: (i) neuroticism would be positively related and conscientiousness would be negatively related to the risk of sexual addiction, and (ii) the risk for sexual addiction, as based on BYSAS scores, would differ among heterosexuals, bisexuals, and gay men.…”
mentioning
confidence: 99%